Biochemical and microbial qualities of Sardinella fimbriata - Immaculate, J. (2016)
Normally sardines are unhygienically sun dried by keeping on the seashore, on mats or palm leaves. In the present study the biochemical and microbial qualities of fresh sardine (Sardinella fimbriata), naturally sun dried, hygienically sun dried using solar dryer and fish rack were assessed. The fresh and differently dried samples were bought from the coastal villages near Tuticorin town at Southeast coast of India. The biochemical composition such as moisture, ash and Free Fatty Acid (FFA) content were lower in solar dryer dried samples, whereas the values of protein and lipid were higher. The microbes and pathogens were totally absent in solar dryer dried samples. The results indicate that different drying methods have a significant effect on the biochemical composition of Sardinella fimbriata. The samples dried using solar dryer have comparatively good nutritional value and hygienic status followed by fish rack dried sardine.